2002
DOI: 10.1093/jnci/94.20.1569
|View full text |Cite
|
Sign up to set email alerts
|

VHL Tumor Suppressor Gene Alterations Associated With Good Prognosis in Sporadic Clear-Cell Renal Carcinoma

Abstract: The VHL alteration status may provide useful prognostic information, as a biomolecular marker, for patients with stage I-III clear-cell RCC who have undergone nephrectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
118
7
9

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 225 publications
(148 citation statements)
references
References 26 publications
14
118
7
9
Order By: Relevance
“…We report our original data providing evidence that mutant VHL, as found in most sporadic RCC, triggers NK cell activation. Although the correlation between VHL alteration in sporadic RCC and better survival is still controversial (Yao et al, 2002;Banks et al, 2006;Smits et al, 2008), the absence of VHL mutation is associated with tumor aggressiveness and poor survival (Patard et al, 2008(Patard et al, , 2009. Our evidence that NK cells are activated differently by targets that bear or not VHL mutations are consistent with earlier findings that suggest that somatic VHL alteration is associated with better cancer-specific survival among those patients presenting with early stage (pT1 and pT2) clear-cell RCC (Parker et al, 2005).…”
Section: Mutated Vhl Rcc Cells and Nk Cell Activationsupporting
confidence: 89%
“…We report our original data providing evidence that mutant VHL, as found in most sporadic RCC, triggers NK cell activation. Although the correlation between VHL alteration in sporadic RCC and better survival is still controversial (Yao et al, 2002;Banks et al, 2006;Smits et al, 2008), the absence of VHL mutation is associated with tumor aggressiveness and poor survival (Patard et al, 2008(Patard et al, , 2009. Our evidence that NK cells are activated differently by targets that bear or not VHL mutations are consistent with earlier findings that suggest that somatic VHL alteration is associated with better cancer-specific survival among those patients presenting with early stage (pT1 and pT2) clear-cell RCC (Parker et al, 2005).…”
Section: Mutated Vhl Rcc Cells and Nk Cell Activationsupporting
confidence: 89%
“…Few studies have addressed the issue of clinical impacts of somatic VHL alterations in sporadic RCCs reporting, however, conflicting results [2,15,26]. Brauch et al [2] have showed a significant association between VHL alterations (mutation and methylation) and advanced RCC tumor stage.…”
Section: Discussionmentioning
confidence: 99%
“…This SNP leads to a proline to serine substitution at codon 582 [13,14]. Although C1772T has been shown not to affect the hydroxylation process [15], it might confer susceptibility to RCC and its presence has been demonstrated to correlate with the development of metastases [14]. Here, we evaluated the prognostic significance of such SNP in ccRCC patients.…”
Section: Introductionmentioning
confidence: 99%
“…Diese Daten sind jedoch äußerst widersprüchlich. Während einige Arbeiten eine VHL-abhängige Prognose postulieren [14,20], konnten andere Studien keine Assoziation zwischen VHLFunktion/Mutation und Überleben von kNZK-Patienten erkennen [1,8] versprechend und verdeutlichen die Mög-lichkeiten von Genexpressionanalysen in der Pathologie [6]. Studien über den Zusammenhang zwischen VHL-Mutationen und Genexpressionsmuster fehlen jedoch bisher in der Literatur.…”
Section: Diskussionunclassified